The selective 5-HT1A receptor agonist, NLX-112, exerts anti-dyskinetic and anti-parkinsonian-like effects in MPTP-treated marmosets. (1st May 2020) - Fisher, Ria; Hikima, Atsuko; Morris, Rebecca; Jackson, Michael J.; Rose, Sarah; Varney, Mark A.; Depoortere, Ronan; Newman-Tancredi, Adrian
Abstract: l -DOPA is the gold-standard pharmacotherapy for treatment of Parkinson's disease (PD) but can lead to the appearance of troubling dyskinesia which are attributable to 'false neurotransmitter' release of dopamine by serotonergic neurons. Reducing the activity of these neurons diminishes l -DOPA-induced dyskinesia (LID), but there are currently no clinically approved selective, high efficacy 5-HT1A receptor agonists. Here we describe the effects of NLX-112, a highly selective and efficacious 5-HT1A receptor agonist, on LID in 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated marmosets, a non-human primate model of PD. NLX-112 exhibited modest plasma half-life (~2h) and marked plasma protein binding (96%). When administered to parkinsonian marmosets with l -DOPA (7 mg/kg p.o.), NLX-112 (0.025, 0.1 and 0.4 mg/kg p.o.) reduced LID scores at early time-points after administration, whilst only minimally interfering with the l -DOPA-induced reversal of motor disability. In contrast, the prototypical 5-HT1A receptor agonist, (+)8-OH-DPAT (0.6 and 2 mg/kg p. o.), reduced LID but also abolished l -DOPA's anti-disability activity. Administered by itself, NLX-112 (0.1, 0.2 mg/kg p.o.) produced very little dyskinesia or locomotor activity, but reduced motor disability scores by about half the extent elicited by l -DOPA, suggesting that it may have motor facilitation effects of its own. Both NLX-112 and (+)8-OH-DPAT induced unusual and dose-limiting behaviors in marmoset that resembled 'serotonin behavioral syndrome' observed previously in rat. Overall, the present study showed that NLX-112 has anti-LID activity at the doses tested as well as reducing motor disability. The data suggest that additional investigation of NLX-112 is desirable to explore its potential as a treatment for PD and PD-LID. Highlights: l -DOPA-induced dyskinesia (LID) develops in many Parkinson's disease patients. NLX-112 is a highly selective and high efficacy serotonin 5-HT1A receptor agonist. In MPTP-treated marmosets NLX112 reduced LID without impairing therapeutic activity. NLX-112 by itself exhibited antiparkinsonian activity (decreased motor disability). NLX-112 is a promising drug candidate for treatment of Parkinson's disease.